KONSEPSI ALQURAN TENTANG PENDIDIKAN SEKS PADA ANAK - Erliani, Sa'adah (STAI AL FALAH Banjarbaru, 2018)
Sex education is providing teaching and understanding and clear information to children when they have understood matters related to sex and marriage. Sex education is an effort to teach, raise awareness, and illuminate sexual problems given to children since they understand problems related to sex, instincts, and marriage. Education has a very strategic role in developing Islamic personality in children in accordance with the guidance of Islam. The Qur'an as a guide to the truth-bearing which has a lot of good leads to peace. Therefore, if examined in more depth, many verses of the Koran explain the importance of sex education. Sex education in early childhood is one solution to minimize crime in children. Keywords: Qur'an, Sex Education, Children